Analysis of pyrrolizidine alkaloids in Crotalaria species by HPLC-MS/MS in order to evaluate related food health risks - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Thesis (PhD (Paraclinical Science))--University of Pretoria, 2006.